Development of ethosomes with taguchi robust design-based studies for transdermal delivery of alfuzosin hydrochloride - Prasanthi, D; Lakshmi, P K (International Current Pharmaceutical Journal, 2012)
In the present investigation efficiency of ethosomes as novel lipid carriers for transdermal delivery of Alfuzosin Hydrochloride (AH) has been evaluated. Taguchi robust design method was used for optimization of ethosomal formulations. Phospholipid type, concentration of phospholipid and concentration of ethanol was selected as independent variables and their effect on the dependent variables (entrapment efficiency and flux) was studied. Ethosomal formulation (EA8) with soya phosphatidylcholine (3%) and ethanol 20% were optimized. Vesicles were spherical, unilamellar with smooth surface. The optimized formulation exhibited vesicle size (6.85 ± 1.35µm), zeta potential (-8.14 ± 0.62mv), entrapment efficiency (91.86 ± 3.25%), flux (27.42 ± 0.04µg/cm2/hr), lag time (0.26±0.20hr) and skin deposition (298.01 ± 15.4µg/g). Transdermal flux was enhanced by 6.92 times over drug solution. Vesicle skin interaction studies showed fatty change in the dermis. The formulations were stable at 4°C for 120 days. Results suggested ethosomes as efficient carriers for AH transdermal delivery. DOI: http://dx.doi.org/10.3329/icpj.v1i11.12063 International Current Pharmaceutical Journal 2012, 1(11): 370-375